The Psychometric Properties of the Norwegian version of Teacher’s Report Form (TRF) - Kornør, Hege; Drugli, May Britt (PsykTestBarn, 2011)
Description: The TRF is one of three instruments in Achenbach System of Empirically Based Assessment (ASEBA). Thomas Achenbach and Leslie Rescorla developed the instrument, published in English in its original version in 2001. Torunn S. Nøvik and Sonja Heyerdahl have translated the TRF into Norwegian, published in 2002. Teachers complete the TRF to assess adaptive and maladaptive functioning in school-aged children and adolescents. The Total problem scale forms the basis for various subscales for syndromes or clusters of problems areas. The TRF takes less than 30 minutes to complete. Requirements for users are test-related qualifications, as well as the following professional qualifications: teacher, psychologist, physician or at least a bachelor’s degree or equivalent in health or social subjects. Literature search: Based on a systematic literature search, we included 17 publications from 14 Norwegian studies in this review. The studies had samples from both clinical and general populations, with sample sizes ranging from 16 to 2688. Psychometrics: Two of the included publications reported norm data from representative samples from a Norwegian general population (6-13 years) and from children (6-12 years) in Møre og Romsdal. Three publications reported construct validity in terms of correlations between TRF scores and scores from other instruments. The internal consistency ranged from Cronbach’s α 0.84 to 0.97 in the studies that reported this measure. None of the publications reported data for criterion validity or test-retest reliability. Conclusion: The Norwegian version of the TRF has one national norm data set and one for Møre og Romsdal. The construct validity measures are difficult to interpret due to unclear relevance and small coefficients. Measures of criterion validity were not identified. The domains had good to excellent internal consistency based on several samples, of which one was large. There is no evidence for the Norwegian TRF version’s test-retest reliability. Despite a great number of publications, the body of evidence for the psychometric properties of the Norwegian version of the TRF is incomplete. This should be reflected in the use of judgment in the interpretation of individual scores in clinical practice. Further, future studies using the TRF should continue focusing on psychometric properties, particularly on diagnostic accuracy, but also on construct validity, test-retest reliability and norms.